Augmented Plasma Adiponectin after Prolonged Fasting During Ramadan in Men - Sadegh Feizollahzadeh; Javad Rasuli; Sorayya Kheirouri; Mohammad Alizadeh (Tabriz University of Medical Sciences, 2014)
Background: Intermittent fasting during Ramadan entails major changes in metabolism and energy expenditure. This study sought to determine effect of the Ramadan fasting on serum levels of adiponectin and tumor necrosis factor-α (TNF-α) as two inter-related peptides involved in cells sensitivity to insulin and glucose metabolism. Methods: Total of seventy healthy men, with age range equal or greater than 30, with at least three type2 diabetes mellitus (DM) risk factors were selected. Serum lipid profile, anthropometric indices and plasma glucose levels were determined using conventional methods. Also, serum adiponectin and TNF- α concentrations were assessed using Enzyme-linked Immunosorbent Assay. Data were analyzed by paired t-test. Results: Ramadan fasting resulted in a significant increase of serum adiponectin (P< 0.000), fasting glucose (P< 0.000) and triglycride (P< 0.001). Body mass index was lowered during the fasting (P< 0.000). Finally, no remarkable decrease was found in serum TNF-α levels (P= 0.100). Conclusion: Ramadan fasting resulted in augmented adiponectin levels which may help in improving metabolic stress induced by insulin resistance in men with predisposing factors of type2 DM.